2020
DOI: 10.1055/a-1073-7941
|View full text |Cite
|
Sign up to set email alerts
|

Total and Regional Body Composition of NCAA Division I Collegiate Basketball Athletes

Abstract: This study aimed to examine body composition using dual X-ray absorptiometry (DXA) in male and female NCAA Division I collegiate basketball athletes. Two-hundred ten (male [M]/female [F]=88/122) basketball athletes’ total and regional fat mass, lean mass, bone mineral density, and visceral adipose tissue were measured. Athletes were classified as: point guards (M/F=27/34), shooting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In American football, "mirroring" positions, such as opposing offensive and defensive positions, demonstrate similar total and regional LSTM measurements, while football athletes in other "non-mirroring" positions have significant regional LSTM and FM differences [15,16]. In collegiate male basketball athletes, centers demonstrate the highest arm and leg LSTM and FM compared to all other positions except power forwards [21]. These observations suggest there may be a relationship between measures of total and regional body composition and sport-and position-specific demands (i. e., kicking, shooting, speed).…”
Section: Total and Regional Lean Soft Tissue Mass (Lstm)mentioning
confidence: 94%
See 3 more Smart Citations
“…In American football, "mirroring" positions, such as opposing offensive and defensive positions, demonstrate similar total and regional LSTM measurements, while football athletes in other "non-mirroring" positions have significant regional LSTM and FM differences [15,16]. In collegiate male basketball athletes, centers demonstrate the highest arm and leg LSTM and FM compared to all other positions except power forwards [21]. These observations suggest there may be a relationship between measures of total and regional body composition and sport-and position-specific demands (i. e., kicking, shooting, speed).…”
Section: Total and Regional Lean Soft Tissue Mass (Lstm)mentioning
confidence: 94%
“…Specifi cally, off ensive and defensive linemen have demonstrated the lowest U/L LSTM ratios, indicating higher relative lower-body LSTM, while quarterbacks and punters/kickers have exhibited the highest U/L LSTM ratio [ 16 ] . Collegiate female basketball athletes also demonstrate ratio diff erences across positions [ 21 ] . The U/L LSTM ratio is highest in point guards and lowest in power forwards and centers.…”
Section: Body Compositionmentioning
confidence: 98%
See 2 more Smart Citations
“…Petway et al (2020) reported on the motor and physiological indicators in national, sub-elite, and junior basketball players, taking into account their position on the court and the match duration (divided into quarters). Much attention has also been paid to the body build and body composition of basketball players and their somatotype (Buśko et al, 2017;Gerodimos et al, 2005;Raymond-Pope et al, 2020;Viswanathan et al, 2010). Almost all studies in the scientific literature are related to tournaments for hearing competitors.…”
Section: Introductionmentioning
confidence: 99%